STRATEGI GURU DALAM MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN BAHASA ARAB DI SMA YASPI JAKARTA - Kamilah, Maya; Hinggil Permana; Agus Susilo Saefullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of information technology, especially social media, has made it easier for the younger generation to access and understand religious information. This article examines the role of social media such as Instagram, YouTube, and Facebook in spreading the values ​​of religious moderation through a qualitative approach based on literature studies. The results of the study show that social media is effective as an educational tool to form a tolerant, inclusive, and balanced religious attitude. Creative and interactive digital da'wah content encourages the internalization of moderation values ​​and forms a virtual community that supports the spread of peaceful da'wah. Thus, social media plays an important role in religious education and is expected to be able to create a harmonious society through a moderate understanding of religion.